Pengaruh Online Customer Review, Live Streaming Selling, dan Flash Sale terhadap Impulsive Buying pada Aplikasi TikTok Shop : (Studi Kasus Mahasiswa UINSU) - Sri Mulyana; Nuri Aslami; Tri Inda Fadhila Rahma (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of online customer reviews, live streaming selling, and flash sales on impulsive buying on the TikTok Shop application with a case study of UINSU students. This study uses a quantitative approach with an associative method. The data used is primary data obtained through a questionnaire distributed to 100 UINSU student respondents who have made purchases on TikTok Shop. Data analysis was performed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 4.0 application. The results showed that online customer reviews had a negative and significant effect on impulsive buying. Meanwhile, live streaming selling and flash sales have a positive and significant effect on impulsive buying. These findings indicate that digital marketing strategies on TikTok Shop, particularly live streaming selling and flash sales, can increase the tendency for impulsive buying among students, while the presence of online customer reviews tends to encourage consumers to be more rational in making purchasing decisions.